Effect of Different Natural Herbal Products on Roughness of Eroded Enamel Surface (An in Vitro Study) - Zeina Samir; Aisha Akram Qasim (University of Mosul, College of Dentistry, 2023)
Aims: The current study aimed to evaluate and compare the effects of the herbal medicaments (Neem, Ginger, Green tea, Clove oil, and peppermint oil) and traditional fluoride gel on the surface roughness of the eroded enamel samples of permanent teeth in vitro study. Materials and methods: A total of (80) sound maxillary permanent first premolars were used in the study. Enamel blocks were prepared and divided into eight groups: Negative control group (C-ve) (n=10) not exposed to Pepsi drink. The remaining samples exposed to Pepsi drink then subdivided into (7) subgroups: Positive control group (C+ve) (Pepsi group), the remaining groups representing different experimental remineralizing agents used as follows: Group 3 (NaF gel), Group 4 (Neem), Group 5 (Ginger+ Manuka honey), Group 6 (Green tea), group 7 (Clove oil) and group 8 (Peppermint oil). The Roughness of enamel surface blocks was measured before and after the PH cycle by using a measurement machine. Results: The surface roughness of all study groups was increased after eroding by Pepsi drink due to the demineralization, then decreased after treatment with remineralizing agents but the highest decrease of the surface roughness measurements belonged to the NaF group followed by Neem and Ginger +manuka honey groups, while the control negative group of deionized water which not exposed to Pepsi drink had no change in the surface roughness measurements. Conclusions: NaF gel group was significantly better than other groups against demineralization and preserving enamel roughness.